Competence Cognition and Its Influence on Supervisors’ Job Satisfaction: A Perspective of Guest Houses in Mombasa County, Kenya - Kivuva, Alex Kyalo; Nzioka, Alice Mueni; Pepela, Anthony Wekesa (American Research Institute for Policy Development, 2019)
Competence is the extent to which an employee can perform work activities skillfully and with the required knowledge.Competence is critical for guest house supervisors. This is because, compared to classified hotels, guest houses, which command a greater patronage,have a larger percentage of untrained personnel. For staff with hospitality training, they at best, serve as supervisors. This study sought to determine the influence of competence, a dimension of psychological empowerment, on job satisfaction of guest house supervisors. A descriptive survey study design, focusing on the seventy-six registered guest houses in Mombasa County was utilized. The study adopted census, where all the supervisors in all the registered guest houses in Mombasa County were included in the research. Primary data was collected through a semi-structured questionnaire.Pearson correlation coefficient and linear regression were used to establish the relationship between the study variables. Findings revealed that there existed a positive and significant influence (p< 0.05) of competence on job satisfaction (r= 0.554). Other than guest house owners and managers, this study will be helpful to organizations under the Ministry of Tourism in sensitizing their members on the importance of the supervisors’ competence tenet of psychological empowerment in discharging their work roles
Keywords: Competence; Psychological Empowerment; Job Satisfaction; Guest houses; Supervisors